Level flight performance determination using collective pitch - Duarte Gomes, A.; Andrade, D. de; Bringhenti, C. (My University, 2014)
Using "Non-Dimensional" parameters for measuring and presenting the level-flight performance of Turbine-Engined Helicopters is very efficient when conducting a flight test performance program. In this study, the level-flight performance of a helicopter-example (AS 550 Fennec) is determined using the collective pitch position as main parameter and the methodology described by the Engineering Sciences Data Unit ESDU No. 74042. The purpose of this study is threefold. The first is to present graphics of level-flight performance for a helicopter-example (AS 550 Fennec) using collective pitch position. The second is to present the relationship between the torque curve and collective pitch. The last is to exemplify some cases where this methodology can be applied to produce level flight performance graphics for operating data manual of a helicopter.